2006
DOI: 10.1111/j.1551-2916.2005.00875.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Relative Humidity on the Viscoelastic and Mechanical Properties of Spray‐Dried Powder Compacts

Abstract: Spray‐dried powder compacts exhibit viscoelastic properties such as stress relaxation, creep, and delayed elastic strain. This behavior is attributed to the organic binder, which forms bridges between the particles in spray‐dried granules, thereby affecting their deformation characteristics. The viscosity and distribution of the binder within the powder compact can affect its mechanical and viscoelastic properties. In this study, the powder was conditioned at different ambient relative humidity (RH) levels, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
7
2
Order By: Relevance
“…On the other hand, no significant subcritical crack growth by coalescence of microcracks originating at a defect is needed to reach critical crack size and subsequent fracture in these compacts, because critical crack size is only a little larger than the granules. This last finding contrast to the results reported by other researchers, in which it was found that this fracture mechanism (subcritical crack growth) needed to develop considerably [6][7][8][9][12][13][14] . Although there are important differences between the characteristics of the compacts studied in this paper and those that appear in the literature cited previously (granule size, compact porosity, nature of the material, and particle size distribution), the authors believe that the use of polymer binders in forming the pieces is the most important reason for the pieces to display, during fracture, significant subcritical crack growth or a process zone ahead of the crack tip.…”
Section: Critical Crack Size a And A Relation To The Textural Chacontrasting
confidence: 84%
See 2 more Smart Citations
“…On the other hand, no significant subcritical crack growth by coalescence of microcracks originating at a defect is needed to reach critical crack size and subsequent fracture in these compacts, because critical crack size is only a little larger than the granules. This last finding contrast to the results reported by other researchers, in which it was found that this fracture mechanism (subcritical crack growth) needed to develop considerably [6][7][8][9][12][13][14] . Although there are important differences between the characteristics of the compacts studied in this paper and those that appear in the literature cited previously (granule size, compact porosity, nature of the material, and particle size distribution), the authors believe that the use of polymer binders in forming the pieces is the most important reason for the pieces to display, during fracture, significant subcritical crack growth or a process zone ahead of the crack tip.…”
Section: Critical Crack Size a And A Relation To The Textural Chacontrasting
confidence: 84%
“…Although there is a certain difference between the values obtained by the different procedures, the values of a and a increase monotonically with average granule size. In addition, critical crack size, whether calculated as a or a, was about twice the granule size, in contrast to the results obtained by other researchers, who reported much higher values for this relation [6][7][8][9][11][12][13][14] . The marked effect of granule size on critical crack size and, hence, on bar mechanical strength, σ f (since the effect of granule size on toughness is small) may be expected to manifest itself in certain textural or microstructural, surface and/or internal characteristics of the compact in relation to original granule size.…”
Section: Fracture Work G a C And G C Ccontrasting
confidence: 81%
See 1 more Smart Citation
“…In this work, two pressing parameters, including pressing pressure and water content, were respectively increased to reduce the size and volume of green pores in pressed specimens and thus to facilitate vitrification during firing [14,15]. As shown in Fig.…”
Section: Performance Of Pressing-powder In Pressing and Firingmentioning
confidence: 99%
“…Carneim and Green 8 assumed that models describing the elastic modulus of partially sintered materials could be applied to green bodies but they found that the presence of an organic binder results in nonlinear stress–strain characteristics. Subsequently, Uppalapati and Green 9,10 showed that the stress–strain behavior is complicated by viscoelastic effects during compaction and in subsequent mechanical property measurements of the green bodies. Because of the plasticizing effect of moisture on the glass transition temperature of water‐soluble organic binders, 5,11,12 Uppalapati and Green 10 reported that the strength, fracture toughness, elastic modulus, stress relaxation, and load deformation behavior of ferrite powder compacts containing an organic binder depended on the ambient relative humidity both during compaction and in subsequent testing.…”
Section: Introductionmentioning
confidence: 99%